How the COVID-19 pandemic is affecting paediatric orthopaedic practice in Turkey - Birsel, Sema Ertan (J Child Orthop, 2020)
PURPOSE: Changes to routine clinical approaches during the corona virus disease 2019 (COVID-19) pandemic are necessary to decrease the risk of infection in patients and healthcare providers. Because the treatment of many conditions is time sensitive, it is crucial to modify the management of paediatric orthopaedic cases by minimizing any subsequent morbidity. Our purpose was to describe the different measures and management strategies that have been applied by paediatric orthopaedic surgeons and to show how paediatric orthopaedic practice is affected in Turkey. METHODS: All active practicing members of the Turkish Society of Children’s Orthopedic Surgery (TSCOS) were contacted via telephone and asked to fill out a survey (24 questions). For participants, either an email or web link was sent to their mobile phones. An online survey generator was used. RESULTS: A total of 54 survey responses were collected, for a response rate of 55%. In all, 62% reported a 75% decrease in their outpatient frequency, whilst 75% reported a 75% decrease in their surgery frequency. A total of 86% of the performed surgeries were emergency cases. None of the participants performed elective surgeries, and 61% did not have the consent form specific to COVID. Choice of protective measures have changed considerably; 96% stated that they needed an algorithm to follow for situations such as pandemic. CONCLUSION: This national survey revealed that the COVID-19 pandemic has had a detrimental effect on paediatric orthopaedic practice and practitioner response varies in terms of reactions and precautions. The necessity of creating a protocol based on what we have learned must be taken into consideration. LEVEL OF EVIDENCE: V